2017
DOI: 10.1189/jlb.4mr0217-048rr
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytes as modulators of dendritic cell function

Abstract: Effector T cell development is directly driven by APCs, in particular, by antigen-primed dendritic cells (DCs). Depending on the pathogenic stimulus and the microenvironment, DCs induce proliferation and polarization of naive CD4 T cells into different effector subsets, such as Th1, Th2, Th17, or regulatory T cells (T). During inflammation, DCs are found in close proximity to other innate immune cells, including all granulocyte subtypes, which potentially influence the immunomodulatory capacities of DCs. Neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 208 publications
(310 reference statements)
0
54
0
Order By: Relevance
“…In the present study, we could show that ECP‐treated neutrophils do not contribute to T cell activation and that activation of T lymphocytes by other stimuli can be suppressed by ECP‐treated neutrophils, showing a potential mechanism of how they can further contribute to ECP's clinical efficacy. Neutrophils may have different immunomodulatory effects on DC function, which can be mediated via cell‐cell contact, soluble factors, neutrophil extracellular traps, and ectosomes . There have been controversial theories on the effects of neutrophils on DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we could show that ECP‐treated neutrophils do not contribute to T cell activation and that activation of T lymphocytes by other stimuli can be suppressed by ECP‐treated neutrophils, showing a potential mechanism of how they can further contribute to ECP's clinical efficacy. Neutrophils may have different immunomodulatory effects on DC function, which can be mediated via cell‐cell contact, soluble factors, neutrophil extracellular traps, and ectosomes . There have been controversial theories on the effects of neutrophils on DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils may have different immunomodulatory effects on DC function, which can be mediated via cell-cell contact, soluble factors, neutrophil extracellular traps, and ectosomes. 39 There have been controversial theories on the effects of neutrophils on DCs. On one hand, neutrophils can attract DCs by the release of chemotactic factors.…”
Section: Neutrophilsmentioning
confidence: 99%
“…The regulation of the innate and adaptive immune systems by neutrophils has been reviewed extensively . Neutrophil granule contents participate in many regulatory activities, including those involving T cells, dendritic cells, B cells, and monocytes .…”
Section: Role Of Exocytosis In Neutrophil Functionmentioning
confidence: 99%
“…The regulation of the innate and adaptive immune systems by neutrophils has been reviewed extensively. [70][71][72][73][74][75][76][77][78][79] Neutrophil granule contents participate in many regulatory activities, including those involving T cells, dendritic cells, B cells, and monocytes. 70,72,73,80 The interaction between neutrophils and monocytes is particularly relevant to antimicrobial activity and inflammatory diseases.…”
Section: Role Of Exocytosis In Neutrophil Functionmentioning
confidence: 99%
“…71 In addition, it was hypothesized that neutrophils act as danger sensors by communicating the presence of infection to dendritic cells ( Figure 5B). 72,73 Moreover, several in vivo studies have demonstrated the ability of neutrophils to transport antigen to lymphoid organs, which indirectly or directly promoted antigen cross-presentation to T cells ( Figure 5C). 74,75 Furthermore, it was shown that neutrophils promote maturation and function of NK cells ( Figure 5D).…”
Section: Regulation Of Adaptive Immune Responsesmentioning
confidence: 99%